Christians in Egypt : Orthodox, Catholic, and Protestant communities, past and present - Meinardus, Otto F. A., 1925-2005 (American University in Cairo Press, 2006)
"Drawing on more than four decades of experience studying Christian communities in Egypt, Otto Meinardus offers here a sweeping overview of the principal Christian churches and organizations in Egypt today. For the first time, this wealth of information has been gathered into one volume, making it an ideal introduction to the Orthodox, Catholic, and Protestant denominations that have a presence in Egypt."--Jacket